The neural basis of hazard perception differences between novice and experienced drivers - Gharib, Seifollah; Zare-Sadeghi, Arash; Zakerian, Seyed Abolfazl; Haidari, Mohsen Reza (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
The neural mechanisms underlying hazard perception are poorly understood as to how experience affects it in drivers. In this study we used functional magnetic resonance imaging (fMRI) to examine experienced-related changes in brain activation of a hazard perception skill between novice and aged drivers. Additionally, region of interest (ROI) and seed-to-voxel analysis were conducted to examine experienced-related functional connectivity changes in visual attention and saliency networks between novice (n=15, age 22.13± 3.38 years years) and experienced (n=16, age 41.44± 5.83 years) drivers. Experienced drivers had significantly lower hazard perception reaction time (1.32 ± 1.09 s) and miss rates (11.42 ± 8.36 %) compared to the novice (3.58± 1.45 s and 39.67 ± 15.72 %, respectively). Blood oxygen level dependent (BOLD) activation increased in occipital, parietal and frontal areas when executing hazard perception task in the both the groups. During task execution, experienced drivers showed, in general, greater activation in occipital lobe, Supramarginal Gyrus (SMG), right insular cortex, and anterior cingulate cortex (ACC) and cerebellar regions compared to the novice drivers indicating more efficient visual attention and decision-making processing in hazard perception skill. Seed based functional analyses in the task revealed greater connectivity between the ACC and the entire salience network (visual attention network) in the experienced group. Additionally, ACC had higher functional connectivity with right frontal eye field (FEF) and, bilateral Intraparietal Sulcus (IPS) and lateral occipital areas in the experienced group. Our results suggest that the hazard perception ability in experienced drivers is due to increase in the activation of executive attention regions, and better functional connectivity between bilateral occipital cortices and salience network. Better hazard perception performance is highly dependent on emotional awareness and attention to the velocity of motion.
an fMRI study
EXCLI Journal;Vol. 19 2020
Keywords: Hazard perception skill; fMRI; Novice drivers; Experienced drivers; 610